Poverty of Spirit within Party and Hookup Culture: Undergraduates' Engagement with Johann Metz - Beste, Jennifer Erin (Horizons, 2017)
In his work Poverty of Spirit, Johann Metz depicts Jesus Christ as embodying three aspects of poverty of spirit required to become fully human: (1) an affirmation of interdependence on God and others, (2) self-love (accepting human finitude and one's unique calling), and (3) love of neighbor as self. Drawing on a qualitative analysis of 150 students' reflections on poverty of spirit within the context of party and hookup culture, this article explores the challenges US undergraduates face in following Christ's path of full humanity. Undergraduates' own insights issue an urgent call to Catholic universities to respond proactively to the dehumanization, injustices, and forms of violence present in party and hookup culture. At stake is the integrity of Catholic higher education's mission to care for the whole person and form students into men and women "for others" who are committed to justice, solidarity, and the common good.